Identifying scalable policy solutions: A state-wide cross-classified analysis of factors related to early childhood literacy - Robert L. Vagi; Clarin Collins; Terri Clark (Arizona State University, 2017)
Given the critical role that literacy plays in children's academic and personal development, policymakers have increasingly focused on policies related to early childhood literacy, particularly among poor and minority students. In this study, authors use a census of data from Arizona, a state with a large and growing population of traditionally low-performing demographic groups, to identify school, district, and community health factors that plausibly influence third grade literacy rates. Authors find two independent measures of student attendance related to school-level reading achievement after controlling for a variety of factors that have been identified in previous studies of student achievement. The findings indicate that policies aimed at increasing school-level attendance rates may be effective and inexpensive approaches to increasing childhood literacy rates.